COVID-19 in third trimester of pregnancy - JosnaVinutha Yadiki; Sultan Abdulkarim Ali Alftaikhah (Wolters Kluwer Medknow Publications, 2023)
The COVID-19 pandemic disease, which affects the respiratory system and produces flu-like symptoms, is caused by the SARS-CoV-2 virus. It is transmitted by close contact, oronasal secretions, or droplets. In general, pregnant individuals are at increased risk than nonpregnant individuals for developing serious SARS-CoV-2 virus-related illnesses, particularly during the third trimester. Despite the lack of research on COVID-19-infected pregnant mothers, this review article has discussed the clinical and laboratory characteristics and impact of COVID-19 on delivery, management, and vaccination of pregnant individuals with COVID-19 infection.